LIKUIDITAS SEBAGAI PEMODERASI PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2013 - 2016) - Tirza Amelia Hestiwardani, 14.05.52.0085; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
This study aimed to determine the effect of profitability, leverage, and liquidity on dividend policy, Determine the effect of profitability and leverage on dividend policy with liquidity as moderating variable. The population in this study are all companies listed on the Indonesia Stock Exchange in 2013 until 2016. The sample of this study was taken by using purposive sampling technique, so that these were 192 companies got for this study. Data analysis tools used in this research is multiple linear regression analysis and Moderate Regression Analysis (MRA). The results showed that the profitability has significantly positive influence on dividend policy, while leverage has significantly negative affect on dividend policy, and liquidity has significantly negative influence on dividend policy, liquidity is not able to moderate the profitability on dividend policy, and liquidity is able to moderate the leverage on dividend policy. Keywords : Profitability, Leverage, Liquidity, Dividend Policy.